Effects of Family Function on Blood Sugar Control in Patients with Type 2 Diabetes Mellitus - Yayuk Fathonah; Ana Fauziyati; Muhammad Malik; Muhammad Hanif (Faculty of Medicine, Public Health, and Nursing, 2021)
Background: A long term treatment can happen for patients with diabetes mellitus (DM), which can negatively affect their lives and their families. Family support is an important factor to help them adapt to their DM and maintain their self-management. Doctors must assess family function of the patients with DM during their treatment.Objective: This study aimed to observe the effects of family function on blood sugar control in type 2 DM patients who were included in PROLANIS (chronic disease management program) at Puskesmas Banguntapan 2 Bantul, D.I. Yogyakarta, Indonesia.Methods: This quantitative analytical study was conducted with a cross-sectional design in November-December 2019 by using the Family APGAR instrument and fasting blood sugar tests from the DM patients’ venous blood. Its sampling technique was the total sampling of the PROLANIS participants who suffered from DM and met inclusion criteria of this study. All obtained data of this study were analyzed by Spearman Product Moment analysis to determine the effects of family function on their fasting blood sugar levels.Results: This study found that there was a significant effect of family function on blood sugar control in the patients with type 2 DM (p=0.008). This finding indicated that the family function was an important aspect in controlling their blood sugar.Conclusion: The family function was an influential factor to optimize the treatment of patients with type 2 DM. The assessment on the family function should be a part of their routine examination in primary healthcare units.